The Impact of the 2013 Curriculum on the Development of 21st Century Attitudes in Elementary School Students - Edward Keith; Mega Melani Ramadani (Yayasan Azhar Amanaa Yogyakarta, 2024)
This research evaluates the impact of the 2013 Curriculum (Kurikulum 2013 or K13) on critical thinking, creativity, collaboration, and digital literacy in Indonesia. Using qualitative methods, including classroom observations, teacher interviews, and student focus groups, the study finds that K13 effectively enhances students' critical thinking and creativity through project-based and thematic learning. Collaborative activities also improve communication and teamwork skills. However, challenges such as inconsistent teacher preparedness, resource disparities, and limited technology access affect the curriculum's implementation. The study underscores the need for better teacher training, equitable resource distribution, and improved digital access to fully realize the benefits of K13.